Uso de dentifrícios fluoretados por crianças: conhecimentos dos pais sobre efeitos preventivos e adversos - Silva, Malena Morais Castro e [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The unmonitored use of fluoridated dentifrices by children under 6 years of age has been considered as a risk factor for the development of dental fluorosis. Therefore, actions to educate parents and guardians of children in the age risk for the development of dental fluorosis are important. The objective of the present study was to evaluate the knowledge of the parents/guardians of children from 0 to 5 years of age about their knowledge on the preventive and adverse effects of the use of fluoridated dentifrices by their children. The project was carried out in three vaccination centers in the city of Araçatuba. A structured questionnaire was applied to parentes/guardians, which contained questions about the interviewees' scholar background, date of birth of the child, gender, neighborhood of residence and aspects related to the use of dentifrice. To evaluate the amount of toothpaste placed on the toothbrush, a toothbrush holder was developed containing 7 toothbrushes with varying amounts of biscuit simulating the toothpaste, determined by weighing dentifrices on a precision scale. It was also questioned whether the child had the habit of eating toothpaste directly from the dentifrice tube and/or swallowing the toothpaste during toothbrushing, brushing frequency and brand of toothpaste used. Finally, questions about the possible adverse effects of fluoride were asked. At the end of the questionnaires, an explanatory pamphlet containing information about the subject was given, at which time the interviewer answered any questions that the interviewee had. The results were submitted to descriptive analysis, Mann Whitney, Kruskall Wallis and Dunn tests, and Spearman's correlation coefficient (p <0.05). The interviewee's education was directly related to his/her knowledge about preventive and adverse effects on the use of fluoridated dentifrices...

O uso não monitorado de dentifrícios fluoretados por crianças abaixo de 6 anos de idade tem sido considerado como fator de risco para o desenvolvimento da fluorose dentária. Por isso, é importante ações para alertar e educar os pais e responsáveis das crianças na faixa etária considerada de risco para o desenvolvimento da fluorose dentária. O objetivo do presente trabalho foi avaliar o conhecimento dos pais/responsáveis de crianças de 0 a 5 anos de idade sobre seus conhecimentos de efeitos preventivos e adversos do uso de dentifrícios fluoretados por seus filhos. O projeto foi realizado em três postos de vacinação da cidade de Araçatuba. A abordagem de 398 pais/responsáveis pelas crianças atendidas nos postos foi feita por meio de um questionário estruturado, o qual continha questões sobre a escolaridade dos entrevistados, data de nascimento da criança, gênero, bairro de residência e aspectos relacionados ao uso de dentifrício. Para a avaliação da quantidade de dentifrício colocada na escova, foi desenvolvido um estojo porta-escovas contendo 7 escovas de dente com quantidades variadas de biscuit simulando o dentifrício, determinadas por meio de pesagem de dentifrícios em balança de precisão. Também foi questionado se a criança tinha costume de comer pasta diretamente do tubo do dentifrício e/ou hábito de engolir o dentifrício durante a escovação, frequência de escovação e marca do dentifrício utilizado. Por fim, foram feitas questões de conhecimento sobre possíveis efeitos adversos do flúor. Ao término dos questionários foi entregue um folheto explicativo, que continha informações acerca do assunto, oportunidade na qual o entrevistador respondeu aos eventuais questionamentos que o entrevistado tinha. Os resultados foram submetidos a análise descritiva, testes de Mann Whitney, Kruskall Wallis e Dunn, e coeficiente de correlação...
Keywords: Dentifrícios; Fluorose dentária; Criança; Educação em saúde; Dentifrices